Petrological Features of Neogene Ulukale Porphyritic Dome and Caglarca Radial Dykes in the Tunceli Volcanic, Eastern Turkey - Kurum, Sevcan; Sar, Abdullah; Yurt, Muhammed Yasir; Yildirim, Ismail (Maik Nauka/Interperiodica/Springer, 2024)
This study presents new analytical data for the Ulukale porphyritic dome located within the Neogene Tunceli volcanic rocks, as well as whole rock geochemistry and Sr-Nd isotope data for the Caglarca radial dykes for the first time. The Ulukale porphyritic dome and the Caglarca radial dykes, have trachyandesite composition. On trace element diagrams normalized to primitive mantle, samples from the dome and dykes have similar features. Whole-rock geochemistry data for the investigated volcanic rocks indicate they formed from low-degree of partial melting of spinel lherzolite at shallow depths. Accordingly magmatism forming the dome appears to have more acidic composition. Sr-Nd isotope data (epsilon Nd(T) value -2.0 and -1.7) for both rock groups indicate a lithospheric subcontinental mantle source. All geochemical data indicate these volcanic rocks had source magma with lherzolitic features which underwent low-degree of partial melting; however, fractional crystallization, magma mixing, contamination in the form of continental crust effects and the effect of subduction-linked sediment melts were shown to be important during magma differentiation. Additionally, all this data shows that these volcanic rocks have the same petrological features as the Tunceli Volcanics, the main product of this magmatism.
Keywords: Tunceli volcanics; Ulukale porphyritic dome; Caglarca radial dyke; Neogene volcanism